(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Introduction The aim of this study is to sum up the current knowledge on the effectiveness of the existing interventions for alleviating loneliness and social isolation among elderly persons. Methods We used a systematic approach and performed a literature search of MEDLINE, ISI Web of science, SCOPUS, The Cochrane Library, and CINAHL databases. After identifying 13 eligible reviews addressing interventions of our interest, we proceeded with a narrative description of the study findings. Results The initiatives largely encompassed one-to-one interventions, group activities or community engagement approaches. In particular, technology interventions were recently given much attention. Overall, the studies showed non-satisfying methodological quality and their results were often inconclusive. Conclusions Although there is a growing body of evidence referring to implementation of interventions targeting social isolation and loneliness among the elderly, future well-designed interventions are necessary in order to draw firm conclusions.